EVALUATING THE EFFICACY OF INTEGRATED MARKETING COMMUNICATIONS WITHIN VETERINARY PHARMACEUTICAL E-COMMERCE - LISYANSKIY, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the dynamic transformation of the veterinary pharmaceutical market in Ukraine under the influence of global digitalization trends, accelerated by the COVID-19 pandemic and the ongoing martial law. These conditions have necessitated rapid adaptation in both B2B and B2C segments, driving veterinary businesses to shift from traditional sales models to electronic commerce formats. The study highlights the significant role of integrated marketing communications (IMC) in this transformation, focusing on their strategic implementation across online and offline channels.Within the B2B segment—comprising farms, veterinary clinics, laboratories, and agro-industrial enterprises—the demand for online ordering systems, electronic product certifications, and detailed technical descriptions has grown substantially. Meanwhile, the B2C segment, represented by pet owners, increasingly values user-friendly e-commerce interfaces, fast delivery, customer reviews, and personalized veterinary recommendations. Their behavior is heavily influenced by mobile device usage, social media content, and impulse-driven purchases during animal health crises.IMC strategies are presented as a cohesive framework that integrates all communication efforts to deliver consistent brand messaging, build trust, and foster customer loyalty. The article emphasizes the synergy created through the integration of digital tools—such as SEO, email marketing, influencer engagement, and social media advertising—with traditional offline tools like exhibitions, printed brochures, and in-person sales consultations. This omnichannel approach allows companies to accompany customers at every stage of their journey, from brand discovery to post-sale support.The research also discusses the role of CRM systems in synchronizing online stores with customer databases to enable personalized marketing, automated feedback, and intelligent remarketing. Additionally, the effectiveness of IMC is assessed using a comprehensive system of metrics that includes economic indicators (ROI, CAC, CPA), behavioral metrics (click-through rate, engagement), and long-term metrics like customer lifetime value (CLTV) and repeat purchases.The study concludes that a well-structured and data-driven IMC strategy is essential for veterinary businesses to remain competitive in the digital economy. It not only enhances customer experience and operational efficiency but also creates sustainable competitive advantages through trust, relevance, and communication consistency across all touchpoints. Social media, in particular, emerges as a strategic communication hub that amplifies brand presence and supports community building around veterinary care. This makes IMC not just a communication tool, but a core element of digital business strategy in the veterinary pharmaceutical sector.
Keywords: integrated marketing communications; e-commerce; social media; content marketing; digital strategies; CRM system; B2B; B2C; omnichannel